Tone and melody in a Congolese popular song - Carrington, John F. (International Library of African Music, 1966)
The accession to power of Lieutenant-General Joseph D. Mobutu as President of the Congo Democratic Republic in November 1965 was followed by the appearance on the market of a popular song in Lingala, one of the linguae francae of the Republic. This song, emphasizing the presidential decision to take over control of the country for a period of five years to ensure peace by a strong military government, and so attempt to redress the economic situation, was diffused regularly over the national radio and became the signature tune used in connection with news bulletins throughout the early part of 1966. If it has not been heard so frequently recently, this may be because recent governmental changes, notably in the person of the prime minister, have rendered part of the song inapplicable to present-day conditions.
Keywords: Popular music; Ethnomusicology; Songs; Lingala language; Republic of the Congo (Léopoldville); African Music